STUDIES OF NOCARDIOSIS IN CATTLE 1 - ISOLATION OF NORCARIDA ASTEROIDES FROML MASTITIS IN CATTLE - MJ. Alwan; A.S. Al~Abaitii; S.Sh. Barhoom (The Iraqi Journal of Veterinary Medicine, 2022)
A six months survey (2-8/1994) was canied out to determine norcaiidal mastitis in cattle in certain dairy herds. A total 126 milk samples collected from mastitic‘ cows and milk tank. Of which 10 from Al-Khalis station, 15 from A1-Wahda station, 6 from White Good village, 90 from Al-Dejaila station and 5 fromMilktauk. Examination of the samples result in isolation of Norcaitlia asteroides from Al-Dejaila station.